Reproductive status of the swordfish, Trichiurus lepturus (Teleostei, Trichiuridae), exposed to small-scale fishing on the north coast of Santa Catarina state, southern Brazil - Paulo de Tarso Chaves (Biotemas, 2009)
The swordfish, Trichiurus lepturus, caught by small-scale fishermen from a community of southern Brazil was investigated based on 398 individuals landed from August 2006 to August 2007, aiming to evaluate in which periods and fishing techniques the reproductive individuals of this species are most exposed to fishing activities. The analysis took into consideration the length of individuals, the morphological attributes of their gonads, the Gonadossomatic Index (GSI), and the kind of gear used in the catches. It was estimated that females mature for the first time at a total length of 75.0cm, and males at 64.0cm. Gillnets and bottom trawling were efficient for the capture of both young and adults, but reproductive individuals were registered only in gillnets. Oocyte hydration and post-spawning in females, the occurrence of mature gonads in males and the values of GSI indicate that “fundeio” and “caceio” (different types of gillnets) are acting on reproductive individuals throughout the entire year, with maximum intensity in spring and summer. Considering that in the studied region fisheries are closed for shrimp bottom trawling in spring, it is suggested that the use of gillnets during spring and mainly summer should be reduced, thus improving the spawning process.